PEMETAAN TINGKAT BAHAYA BENCANA LONGSOR DAN SISTIM PERENCANAAN TATA LETAK BANGUNAN DALAM TATA RUANG WILAYAH KOTA BAUBAU - Idham Handa; Taufik Taufik (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
The study analyzes the level of landslide-prone and distribution and formulates the direction of the building layout information system to avoid landslide hazards. This research used quantitative descriptive design and survey design. The object of analysis is the slope of the slope, land use, type of soil, rainfall, geology, infrastructure, the presence of faults or faults, and gawir and settlement density. Data were analyzed by descriptive qualitative and spatial analysis (ArcView 3.2). Landslide hazard in Baubau City in the "safe" category was 17,515.47 ha, "low prone" was 11,185.43 ha and kerawana "medium" was 60.94 ha. The directive on the spatial planning of buildings in the City of Baubau for "safe" areas is allowed for building construction. Areas with "low" potential are allowed for building construction activities while maintaining protected areas or 30% open space, while areas with "medium" potential are allowed for building construction activities while maintaining protected areas or 30% open space and tightening permits for building operations.